2010
DOI: 10.3109/10428194.2010.494316
|View full text |Cite
|
Sign up to set email alerts
|

Silent hypersensitivity toEscherichia coliasparaginase in children with acute lymphoblastic leukemia

Abstract: This prospective study aimed to assess the incidence of silent hypersensitivity to Escherichia coli asparaginase in the treatment of acute lymphoblastic leukemia (ALL). Thirty-three children with newly diagnosed ALL were included in the study and treated according to the FRALLE 2000 protocol. The 'A group' (n = 18) differed from the 'B-T group' (n = 15) by a less intensive chemotherapy, the absence of concurrent prednisone therapy, and different asparaginase administration modalities during the second intensif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…18 This cut-off of ≥ 0.1 IU/mL has been confirmed and used in many clinical trials. 9,19,[22][23][24] The question arises whether a lower threshold, for example of 0.05 IU/mL, also leads to complete asparagine depletion. Rizzari and colleagues showed that trough asparaginase activity levels of < 0.05 IU/mL, obtained either with native E. Coli or Erwinia asparaginase, resulted in serum and CSF asparagine depletion in children with ALL.…”
Section: What Defines Optimal Asparaginase Activity?mentioning
confidence: 99%
“…18 This cut-off of ≥ 0.1 IU/mL has been confirmed and used in many clinical trials. 9,19,[22][23][24] The question arises whether a lower threshold, for example of 0.05 IU/mL, also leads to complete asparagine depletion. Rizzari and colleagues showed that trough asparaginase activity levels of < 0.05 IU/mL, obtained either with native E. Coli or Erwinia asparaginase, resulted in serum and CSF asparagine depletion in children with ALL.…”
Section: What Defines Optimal Asparaginase Activity?mentioning
confidence: 99%
“…8,12 These were characterized by insufficient ASE activity because of inactivating Abs. Because silent inactivation can be detected by measuring the ASE activity in the serum, investigators in the ALL-BFM trials implemented monitoring of ASE activity more than a decade ago.…”
Section: Introductionmentioning
confidence: 99%
“…(10, 12-16) Erwinia ASNase was associated with less allergic reactions when compared to both PEG ASNase and native ASNase during IM #1 only. In all other phases of therapy, there was no significant difference in incidence of allergic reactions.…”
Section: Discussionmentioning
confidence: 95%